“INSON” QASİDASİDA INSON MA’NAVIY MUKAMMALLIGI VA ICHKI KURASHI (TAMADDUN NURI JURNALI, 2024)
In the poem "Insan" ("Human"), the poet highly values human moral virtues. The themes of self-discovery, resilience in the face of hardship, and remaining true to one's principles are central to the work. Erkin Vahidov emphasizes the purpose of human life and the individual's role in society, inviting readers to reflect and discover their inner strength. The theme of "humanity" holds a special place in Erkin Vahidov’s work, rich and profound in its philosophical content. In each stanza, the poet poetically expresses an individual's personal responsibility, attachment to the homeland, nature, and the world, as well as the need to strive for progress and peace.